PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN: Studi pada PT. Gapura Angkasa Cabang Denpasar - Ni Komang Mia Widiastini; Putu Yudy Wijaya; I Gede Aryana Mahayasa (Universitas Triatma Mulya, 2023)
High competence and the right organizational culture are the keys to high employee performance. Employee performance at PT. Gapura Angkasa Denpasar Branch is an important factor so that the company can run normally. The purpose of this study was to determine competence and organizational culture on employee performance. This research was conducted at PT. Gapura Angkasa Denpasar Branch with a total population of 469 employees. Determination of the number of samples was carried out using the slovin formula so that the number of samples was determined to be 82 employees. The number of samples taken was 82 respondents. Primary data collection is done by using a questionnaire. The data analysis technique uses multiple linear regression analysis. Based on the results of the analysis, it can be concluded that (1) competence has a positive and significant effect on employee performance, (2) organizational culture has a positive and significant effect on employee performance, (3) competence and organizational culture simultaneously have a positive and significant effect on employee performance.